Equals in learning and piety: Muslim women scholars in Nigeria and North America - Mack, Beverly (Women in Africa and the Diaspora, 2023)
Equals in Learning and Piety is an intellectual history of the Yan Taru (Associates) movement, a women-led Islamic educational organization that continues to this day in both northern Nigeria and in the United States. Drawing on extensive scholarship across disciplines including history, Islamic studies, anthropology, gender and women s studies, and literary studies-and alongside rigorous ethnographic research and interviews with leading Nigerian Muslim scholars-Beverly Mack argues that this formidable Muslim women s movement consolidated the religious and social order established by the Sokoto Jihad in the early nineteenth century. Mack shows how women scholars instructed rural Hausa and Fulani women in Muslim ethics, doctrine, traditions, and behavior that followed and replaced the traumatic experience of warfare unleashed by the Jihad. She shows that these unique social engagements shaped people s agency in the dynamic process of social change throughout the nineteenth century. Women imaginatively reconciled Muslim reformist doctrines and traditional practices in Nigeria, and these doctrines have continued to be influential in the diaspora, especially among Black American Muslims in the United States in the twenty-first century. With this major investigation of a little-studied phenomenon, Mack demonstrates the importance of women to the religious, political, and social transformation of Nigerian Muslim society